Perceptions and attitudes about ornamental characteristics of sub-mediterranean deciduous trees during the winter season - Boris Dorbić; Sandra Dukić; Emilija Friganović; Margarita Davitkovska; Zvezda Bogevska; Ana Vujošević; Sandra Popović (My University, 2018)
The selection of appropriate trees is extremely important whilst designing different landscape surfaces, since it frequently defines both the appearance and the comfort of the open space. Ornamental values of the tree species throughout the year need to be considered. Some deciduous trees can show their ornamental value even during the winter season. Due to one or more ornamental characteristics (habitus, tree bark, tree trunk, branches, twigs and fruits) during the winter season, around 10 species of trees can be highlighted in the sub-Mediterranean climate, which is also the climate in the city of Knin. They include the following tree species: Celtis australis L., Ulmus pumila L., Tilia cordata Mill, Morus nigra L., Aesculus hippocastanum L., Acer negundo L. etc. Consequently, the objective of this paper was to conduct research on perceptions and attitudes about ornamental characteristics and the use of deciduous sub-Mediterranean trees during the winter season. The survey research was conducted in April and May of 2017 on a sample of 50 respondents originating from the area of the city of Knin and its outskirts. Based on the findings of the previously mentioned research, the conclusion was reached that the respondents originating from the city of Knin and its outskirts evaluated the ornamental characteristics for the use of eight out of nine selected tree species with the average grade good. The hybrid plane tree referred to as London plane or Platanus x hispanica Münchh received the highest grade. They most probably liked this species due to its unusual appearance (habitus, fruit, tree trunk etc.) and its less frequent use in parks and landscape surfaces. The findings of this research can be used for the purpose of design of different landscape surfaces aimed at increasing user comfort and satisfaction.
Keywords: deciduous trees, winter season, aesthetics, perception, Knin